UMPSA receives delegates from the Johor State Education Department - Siti Nur Azwin, Zulkapri (UMPSA, 2023)
PEKAN, 10 August 2023 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) received delegates from the Johor State Education Department in conjunction with the Industry Verification Visit for the Career Advisor Adoptive Programme of the Johor State Education Department recently.